2016
DOI: 10.1080/07294360.2015.1137887
|View full text |Cite
|
Sign up to set email alerts
|

Student teams’ development over time: tracing the relationship between the quality of communication and teams’ performance

Abstract: Current discussions in higher education and alumni training acknowledge the challenges training programs face in responding to the authentic needs of the labor market. In addition to academic knowledge, higher education institutions are expected to provide general 21st-century skills, such as problem-solving, critical thinking, collaboration, and interpersonal skills. To meet these challenges, many institutions utilize collaborative pedagogies such as learning in teams. However, teamwork in higher education te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…This shows the positive impact of FST as one of the most common fuzzy logic methods used to improve fuzzy logic and a reduction ambiguity in predictions due to the subjective assessment. In each of these methods, 21.05% of the eight articles applying this method have reported positive effects on fuzzy logic (Daud et al, 2011;Henriques et al, 2018;Baba et al, 2012;Voskoglou, 2012;Vesely et al, 2016;Jamali and Sayyadi Tooranloo, 2009;Voskoglou, 2013;Pöysä-Tarhonen et al, 2016), and 2.63% of articles considering the effects of fuzzy method because the results obtained do not make significant changes due to a decrease in some student scores (Ozdemir and Tekin, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows the positive impact of FST as one of the most common fuzzy logic methods used to improve fuzzy logic and a reduction ambiguity in predictions due to the subjective assessment. In each of these methods, 21.05% of the eight articles applying this method have reported positive effects on fuzzy logic (Daud et al, 2011;Henriques et al, 2018;Baba et al, 2012;Voskoglou, 2012;Vesely et al, 2016;Jamali and Sayyadi Tooranloo, 2009;Voskoglou, 2013;Pöysä-Tarhonen et al, 2016), and 2.63% of articles considering the effects of fuzzy method because the results obtained do not make significant changes due to a decrease in some student scores (Ozdemir and Tekin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…• behavior (Vesely et al, 2016), • e-learning (Herrera-Viedma et al, 2009;Dias and Diniz, 2013;Almohammadi and Hagras, 2013;Deborah et al, 2015;Arguedas et al, 2018), • intelligent tutoring system (Chrysafiadi and Virvou, 2012;Machado et al, 2016), • laboratory application (Gokmen et al, 2010; Yıldız and Baba, 2014), • library service quality (Jamali and Sayyadi Tooranloo, 2009), • presentation skills (Daud et al, 2011; Ozdemir and Tekin, 2016), • problem solving (Voskoglou, 2012;Voskoglou, 2013;Owais, 2009), • student academic performance (Ingoley and Bakal, 2012;Yadav and Singh, 2011;Oyelade et al, 2010;Yadav et al, 2014;Sakthivel et al, 2013;Yildiz et al, 2013;Arora and Saini, 2013;Inyang and Joshua, 2013;Rusli et al, 2008;Do and Chen, 2013;Hidayah et al, 2013;Borkar and Rajeswari, 2013), • student learning assessment (Sripan and Suksawat, 2010), • student performance assessment (Barlybayev et al, 2016;Darwish, 2016;Baba et al, 2012;Bhatt and Bhatt, 2011;Prokhorov and Kulikovskikh, 2015;Patil et al, 2012;Pöysä-Tarhonen et al, 2016), and • students' choice (Henriques, et al, 2018;Kabra and Bichkar, 2011).…”
Section: Articles Distribution Based On Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fransen, Kirschner, and Erkens, (2011) argued that high-quality task-specific communication is important in all stages of team work. Pöysä-Tarhonen, Elen, and Tarhonen (2016) and Vora and Markóczy (2012) demonstrated that improved communication in terms of content, frequency, quality, and responsiveness helps to enhance group learning ability and overall task performance. Similarly, Baldwin, Bedell, and Johnson (1997); Chapelain, Morineau, and Gautier (2015); and Pöysä-Tarhonen et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pöysä-Tarhonen, Elen, and Tarhonen (2016) and Vora and Markóczy (2012) demonstrated that improved communication in terms of content, frequency, quality, and responsiveness helps to enhance group learning ability and overall task performance. Similarly, Baldwin, Bedell, and Johnson (1997); Chapelain, Morineau, and Gautier (2015); and Pöysä-Tarhonen et al. (2016) proved that groups with high levels of communication are likely to achieve improved group performance.…”
Section: Literature Reviewmentioning
confidence: 99%